2011
DOI: 10.1111/j.1525-1594.2011.01346.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Fabrication Techniques for Human Adipose Tissue Engineering in Severe Combined Immunodeficient Mice

Abstract: Adipose tissue engineering has been advocated for soft-tissue augmentation and for the treatment of soft tissue defects. The efficacy in terms of persistence of the engineered fat is, however, not yet understood and could depend on the nature of fabrication and application. The high metabolic demand of adipose tissue also points to the problem of vascularization. Endothelial cell (EC) cotransplantation could be a solution. Human adipose tissue-derived stromal cells were seeded on collagen microcarriers and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Maumus et al (2011) have considered how changes in adipose tissue microenvironment may participate in ADSC commitment and contribute to excessive adipose tissue development in obesity. Various studies have also shown that ADSC yield can vary depending on donor site (Du et al 2005;Katz et al 2005;Bunnell et al 2008;Maumus et al 2011;Frerich et al 2012). In our own studies using primary human tissue from other sources, such as skin, we have previously reported variation between tissues from different donors (Jubin et al 2011;Lenihan et al 2014), especially when analysed at the level of gene expression, and this may also explain the large amount of biological variation observed in the qRT-PCR results in this study.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Maumus et al (2011) have considered how changes in adipose tissue microenvironment may participate in ADSC commitment and contribute to excessive adipose tissue development in obesity. Various studies have also shown that ADSC yield can vary depending on donor site (Du et al 2005;Katz et al 2005;Bunnell et al 2008;Maumus et al 2011;Frerich et al 2012). In our own studies using primary human tissue from other sources, such as skin, we have previously reported variation between tissues from different donors (Jubin et al 2011;Lenihan et al 2014), especially when analysed at the level of gene expression, and this may also explain the large amount of biological variation observed in the qRT-PCR results in this study.…”
Section: Discussionmentioning
confidence: 55%
“…In this study we isolated and cultured ADSCs in seven proliferation media as described by various authors (Katz et al 2005;Yoshimura et al 2006;Bunnell et al 2008;Du et al 2010;Zhou 2011;Aoyagi et al 2011;Frerich et al 2012) and two other proprietary media. Rate of proliferation is an important factor for clinical application, where autologous cells are required for reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Due to an expanding world population and to increasing meat consumption in developing economies, it is predicted that meat consumption will double in the coming forty years (FAO, 2006). Although these predictions are associated with considerable uncertainty, the sheer magnitude of this alleged increase supports the assumption that demand will increase appreciably.…”
Section: Introductionmentioning
confidence: 95%
“…This is generally based on concerns about sustainability, environmental burden and animal welfare. These concerns have grown due to further intensification of livestock herding and slaughtering, and on the other hand a predicted rapid increase in global meat consumption (FAO, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, engineered constructs made of ASCs seeded on collagen microcarriers submitted to adipogenic differentiation and enriched or not in endothelial cells and fibrin matrix grafted to SCID mice featured a weight maintenance at 4 weeks in the range of 10% to 37% of the volume measured at day 12. 62 Another study has determined a a Error was calculated based on the standard deviation range of T 1g (the factor having by far the strongest incidence on the results of blood fraction calculated using Equation 6). …”
Section: Discussionmentioning
confidence: 99%